Technological leapfrogging and country strategic patent policy - Yu, Fei; Wu, Yanrui; Chen, Jin; Lewin, Arie Y. (Journal of International Business Studies, 2023)
In this paper, the term “Country Strategic Patent Policy” refers to the case in which the examination of foreign firms’ patent applications may be deliberately manipulated by national patent offices to protect domestic firms, as a means to leapfrogging their foreign counterparts in technological strategic sectors. However, it is empirically questionable to distinguish the impact of discriminatory patent policy from the effect of the liabilities of foreignness. Therefore, international intervention to eliminate discriminatory treatment has been controversial. In this paper, we try to solve this conundrum by proposing a game-theory model to simulate the effect of strategic patent policy. The simulation results suggest that strategic patent policy measures are more likely to impede foreign patents that are (1) associated with R&D-intensive industries, (2) related to sectors where local firms’ absorptive capability is weak, and (3) registered in other countries. These hypotheses are then tested empirically by using patent data bases of six major economies in the world. The empirical analysis provides evidence of the possible existence of strategic patent policy against foreign companies in Japan and China, especially in high-technology and medium-high-technology industries.